Depression and the Quality of Life among Filipino Chemotherapy Patients - Pearl Irish V. De Paz (Universitas Airlangga, 2021)
Introduction: Undergoing chemotherapy has adverse effects to the physical, emotional and mental health of the chemotherapy patient that may cause depression and disturb the quality of the chemotherapy patient's life. Hence, the study aimed to determine the level of depression and the quality of the Filipino chemotherapy patient's life. Methods: The study applied a quantitative descriptive-correlational research design. Purposive sampling was done to identify the 102 respondents, who were Filipino chemotherapy patients admitted in a tertiary hospital in Eastern Visayas from December 2018 to March 2019. The study used standardized questionnaires and these were distributed among the respondents. To analyze the data, descriptive statistics and total scores were used. Likewise, Pearson-Product Moment Coefficient analysis was also used to determine the correlation between the two variables. Results: 102 patients participated in the study. Findings indicated that most of the respondents (52.38%) experienced mild depression and that their quality of life is good (97.05%). However, there were four respondents who experienced moderate depression. Moreover, results also show that there is a strong relationship between the two variables (R=-0.053; P-value=0.000). Conclusion: The study's result highlights the crafting of a home-based care plan that will guide the chemotherapy patients and their families in the prevention of depression. Likewise, it is also aimed in achieving a favorable quality of the chemotherapy patient's life.